A design method for rail profiles based on the geometric characteristics of wheel–rail contact. (May 2018) - Mao, Xin; Shen, Gang
Designing a proper rail profile carries more significance than designing a wheel profile because of the amount of work and cost involved in the maintenance of rails. A better rail profile will not only help to ensure achieving the desired dynamic performance of rail vehicles but it also extends the service life of rails. This paper presents a unique design method for the design of rail profiles based on the given geometric contact characteristics. The proposed method utilizes a given wheel profile and two typical functions respectively to set the main design targets. The first function is the rolling radii difference and the second one is the contact angle difference. Wheel–rail contact distribution is chosen as the secondary target to prevent stress concentration and the associated fatigue failure. With certain assumptions, the solution process becomes a reverse designed one, which can be solved by using proper discrete numerical methods. Two examples of rail profile designs have been discussed in detail for rigid and independent wheelsets.